Development of Silicon Photonics Devices Using Microelectronic Tools for the Integration on Top of a CMOS Wafer. (9th June 2008) - Fedeli, J. M.; Di Cioccio, L.; Marris-Morini, D.; Vivien, L.; Orobtchouk, R.; Rojo-Romeo, P.; Seassal, C.; Mandorlo, F.
Abstract : Photonics on CMOS is the integration of microelectronics technology and optics components to enable either improved functionality of the electronic circuit or miniaturization of optical functions. The integration of a photonic layer on an electronic circuit has been studied with three routes. For combined fabrication at the front end level, several building blocks using a silicon on insulator rib technology have been developed: slightly etched rib waveguide with low (0.1 dB/cm) propagation loss, a high speed and high responsivity Ge integrated photodetector and a 10 GHz Si modulators. Next, a wafer bonding of silicon rib and stripe technologies was achieved above the metallization layers of a CMOS wafer. Last, direct fabrication of a photonic layer at the back-end level was achieved using low-temperature processes with amorphous silicon waveguide (loss 5 dB/cm), followed by the molecular bonding of InP dice and by the processing in microelectronics environment of InPμ sources and detector.